Workspace transitions: conceptualizing and measuring person–space fit and examining its role in workplace outcomes and social network activity. Issue 4 (16th November 2020) - Bankins, Sarah; Tomprou, Maria; Kim, ByeongJo
Abstract : Purpose: Although the physical environment provides an important context for employees' work, there remain divergent findings regarding how different spatial settings, such as more open or more closed workspaces, impact employees. Employing research on the functions of the physical work environment, we contribute to a growing body of research on employees' interactions with their workspace by developing and measuring the notion of person–space fit (P-S fit). This construct affords examination of the multi-dimensional nature of employees' interactions with their workspaces, to understand how their perceived fit with the key functions of their workspace impacts their experiences and social network activity at work. Design/methodology/approach: We first develop a new P-S fit scale and test its factorial, convergent, discriminant, and incremental validity over other person–environment fit concepts ( N = 155). Next, in a naturally-occurring, quasi-field experiment of a workspace change intervention moving employees from predominantly closed workspace to more open workspace ( N = 47 pre-move; N = 37 post-move), we examine how changes in both workspace layout and P-S fit impact workers' experiences of their workspaces (needs for task privacy and spaciousness) and collaborative behaviors (social network activity). Findings: Our P-S fit scale consists of theoretically and empirically validated dimensions representing fit with four workspace functions: aesthetic fit; identity fit; instrumental fit; and collaboration fit. Instrumental fit is positively associated with experiences of task privacy, whereas aesthetic fit and identity fit positively associated with experiences of spaciousness, but no forms of fit were related to social network activity. However, the findings show that work-related social network ties tended to decrease, and new ones were less likely to form, in open office spaces. Originality/value: Contributing to a growing body of research linking person–environment fit literature to workspace design, this study offers a new scale assessing P-S fit and provides some empirical evidence of its importance for understanding the complexity of the employee-work environment interaction.